Kajian Etnomatematika pada Permainan Tradisional Bola Bekel Dalam Pembelajaran Perkalian di Sekolah Dasar - Ala Nabila; S. Supriadi (Universitas Mathla'ul Anwar Banten, 2026)
Traditional games can be used as an alternative learning method that is more relevant to students' experiences. One traditional game related to mathematics is the bekel ball game. This study aims to examine the ethnomathematical elements contained in the traditional bekel ball game and describe its use in teaching multiplication in elementary schools. This study used a literature review method with a qualitative approach. Data were obtained from various journal articles and one thesis relevant to the topics of ethnomathematics, the bekel ball game, and teaching multiplication in elementary schools. The data were analyzed using qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The study results indicate that the bekel ball game contains several ethnomathematical elements, namely the concepts of number, addition, subtraction, multiplication, and geometry. These concepts emerge through play activities such as counting the number of bekel balls, grouping the balls according to the game stages, determining the remaining balls, and recognizing the shapes of the game tools. In teaching multiplication, the bekel ball game can be used to help students understand the concepts of repeated addition and grouping more concretely through direct play experiences. In addition to supporting the understanding of mathematical concepts, the use of marbles can also help increase student involvement in learning while introducing local culture in the elementary school environment.